2007
DOI: 10.1186/gb-2007-8-4-r59
|View full text |Cite
|
Sign up to set email alerts
|

The innate immune repertoire in Cnidaria - ancestral complexity and stochastic gene loss

Abstract: Analysis of genomic resources available for cnidarians revealed that several key components of the vertebrate innate immune repertoire are present in representatives of the basal cnidarian class Anthozoa, but are missing in Hydra, a member of the class Hydrozoa, indicating ancient origins for many components of the innate immune system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
348
2
7

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 333 publications
(377 citation statements)
references
References 55 publications
12
348
2
7
Order By: Relevance
“…The phylogenetic tree, based on the TIR domain, suggested that the molecule can be regarded as the ortholog of vertebrate TICAM1 and TICAM2. To date, no homolog for TICAM-1 or TICAM-2 has been reported in Cnidaria [8], sea urchin [10,11] or other non-chordates, further suggesting that TICAM first emerged in the basal chordates and bbtTICAM might have evolved as the earliest molecule of the ancestral vertebrate TICAM1 and TICAM2.…”
Section: Discussion Bbtticam Is the Earliest Ortholog Of Vertebrate Tmentioning
confidence: 99%
See 4 more Smart Citations
“…The phylogenetic tree, based on the TIR domain, suggested that the molecule can be regarded as the ortholog of vertebrate TICAM1 and TICAM2. To date, no homolog for TICAM-1 or TICAM-2 has been reported in Cnidaria [8], sea urchin [10,11] or other non-chordates, further suggesting that TICAM first emerged in the basal chordates and bbtTICAM might have evolved as the earliest molecule of the ancestral vertebrate TICAM1 and TICAM2.…”
Section: Discussion Bbtticam Is the Earliest Ortholog Of Vertebrate Tmentioning
confidence: 99%
“…The direct interaction of MyD88 with TLRs in Drosophila and amphioxus suggests that this pathway is functionally conserved during evolution [13]. Unlike MyD88, no homolog of TICAM1 or TICAM2 has been identified in non-chordates such as Drosophila, Cnidaria [8], or sea urchin [10,11]. Although TICAM1 orthologs could be found in the early vertebrates lamprey [14] and zebrafish [15][16][17][18][19], they do not function in the same manner as those found in mammals.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations